Care needs of children with chronic illnesses from the perspectives of children, parents, and nurses: a Q methodology approach - Emine Güneş Şan; Rukiye Çelik; Naime Altay (BMC Nursing)
Abstract Background Understanding the care needs of children diagnosed with chronic diseases and their parents is essential for quality nursing care. Aim This study aimed to determine the priorities of the needs of the children diagnosed with chronic diseases, their parents, and the nurses caring for them. Methods This exploratory study was conducted in the Gazi University. Data were collected using the Q methodology approach. 41 people (18 children, 18 parents, and 5 nurses) participated in this study. The study involved 23 cards sorted separately by children (n = 18), their parents (n = 18), and nurses (n = 5). The cards were ranked from (+ 3) to (-3) from “most important” to “least important.” The factor array of each statement, Z score value, distinguished reports (p < .05, p < .01). Results Q factor analysis revealed four factors for children, five for parents, and two for nurses. The essential needs for children are that the nurse should “Be smiling and approachable” and “Provide information about the illness.” Similarly, the necessary need for parents is that nurses “Provide information about the illness”. Conclusion It is essential to know the care needs of children and parents to provide good quality care. Clinical trial number Not applicable.